Foreign Aid and Economic Growth in Sub Saharan Africa - Chilinkhwambe, Tamara (Research of GSB, 2019)
This paper seeks to examine the relationship between foreign aid and economic growth in Sub Saharan Africa (SSA). The study is based on a sample of 21 ‘low income countries’ as defined by The World Bank, and used data covering a 25 year period from 1991 to 2015. The variables in the study are; growth measured by Gross Domestic Product (GDP) per capita as a dependent variable, foreign aid which is represented by Net Official Development Assistance (NODA); macroeconomic variables are trade openness, government capital formation and labour force. The study seeks to answer the question: Does foreign aid contribute to economic growth? The study explores the hypothesis that foreign aid does not promote economic growth in Sub Saharan Africa. To empirically investigate the hypothesis, the approach taken was similar to that of Durbarry, Gemmell, & Greenaway (1998) by employing panel data techniques and crosssection methods and utilized the augmented Fischer-Easterly type model. Similar to Durbarry, Gemmell, & Greenaway (1998), the study sought to identify not only aid effects on growth using a set of conditioned macroeconomic policy variables, but also to test the significance of this set when aid is included as one of the determinants of economic growth. Given that the study employed panel data, the Hausman Chi-Square test was utilized to determine whether to use fixed effects or random effects model. The results favoured fixed effects over random effects hence the model was adopted for empirical analysis. The study finds macroeconomic policy variables (gross capital formation and labour force) have a positive impact on economic growth, and trade openness has a negative impact as measured by annual GDP growth. These results support the theory which argues for the important role labour and capital play in the economic growth of a country. The results also show that foreign aid has a weak positive correlation to growth. These results are significant at 5% error level hence the hypothesis is rejected and it is concluded that foreign aid promotes economic growth in Sub Saharan Africa. Further analysis of time effects test suggest that being in a specific time period has got an impact on growth in Sub Saharan Africa and country effects results indicate that being in a specific country does not have effects on economic of the growth of the country.